ANALISIS INDIKATOR GROSS DEATH RATE (GDR)DAN NET DEATH RATE(NDR) DI RUMAH SAKIT UMUM DAERAH WALED KABUPATEN CIREBON - Reza Noviar; Jaenudin; Loura Weryco Latupeirissa (LPPM ITEKES Mahardika, 2019)
Based on preliminary studies conducted at Waled General Hospital the value of GDR and NDR has increased beyond the ideal standard set by the Ministry of Health, namely for GDR = ≤ 45 ‰ and for NDR = ≤ 25 ‰. The GDR in 2013 was 49.95 ‰, and in 2014 it was 61.10 ‰, while the NDR in 2013 was 19.71 ‰, and in 2014 it was 24.30 ‰. The results of the 2013 and 2014 calculations show the value of the GDR and NDR indicator numbers getting higher year after year. This type of research is a descriptive study. The method used is the observation method. The purpose of this study is to analyze the results of GDR and NDR calculations. Data collection procedures in this study by recording the results of monthly recapitulation of inpatient visits about GDR and NDR in 2013-2017. The population and sample in this study were GDR and NDR records from 2013 to 2017. The time of the study was conducted on 28 July 2018 in Waled County General Hospital. From the observations obtained the value of GDR and NDR in 2013-2017 tends to increase and decrease beyond the ideal limit that has been set. The lowest NDR was in 2013 with a value of 19.71 ‰, and the highest in 2015 with a value of 27.60 ‰. The lowest GDR was in 2013 with a value of 49.95 ‰, while the highest GDR was in 2016 with a value of 64.43 ‰. From the results of the study it is suggested that it is necessary to carry out medical audits and in-depth interventions regarding the improvement of GDR and NDR indicators and graph the GDR and NDR, so that they can always monitor the rise or fall of these indicator numbers, and for planning efforts to improve the quality of health services.